Impact of bile duct stenting on the management of symptomatic choledocholithiasis: a retrospective multicenter analysis - Rebelo, Artur; Tischer, Marie L.; Rosendahl, Jonas; Walldorf, Jens; Mosa, Tawfik; Kleeff, Jörg; Klose, Johannes (Frontiers in Surgery, 2025)
ObjectiveCholedocholithiasis (CDL) can lead to various complications and requires treatment approaches for both biliary tract clearing and cholecystectomy. This study aims to characterize CDL patients, evaluate treatment strategies, assess associated complications, and explore economic impacts.MethodsWe conducted a retrospective analysis of 112 patients between 2016 and 2021 at two centers. We performed a descriptive analysis comparing outcomes of patients undergoing ERCP with and without bile duct stenting. Univariate and multivariable analyses were used to identify factors related to complications.ResultsBile duct stenting was associated with significantly higher complication rates (52.4%) compared to the group without stenting (26.5%) (p = 0.006). Factors influencing stent implantation included prior abdominal surgeries (OR = 03.51, p = 0.02), cholangitis at admission (OR = 03.02, p = 0.032), and bile duct diameter (OR = 01.16, p = 0.057). The overall median length of stay was longer for patients with stenting (19 days) compared to those without (11 days) (p < 0.001). Finally, reimbursements were higher for patients with stenting. Reimbursement for complicated courses was higher than for those without, independent of initial bile duct stenting (with stent p = 0.006, without stent p = 0,003).ConclusionBile duct stenting during CDL management is associated with higher complication rates, longer hospital stay, and increased costs. These associations may reflect both clinical severity at baseline and procedural sequencing. A more restrictive placement of biliary stents might be advisable.